2015
DOI: 10.1016/j.pscychresns.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation between emotion and theory of mind networks in borderline personality disorder

Abstract: a b s t r a c tIndividuals with borderline personality disorder (BPD) commonly display deficits in emotion regulation, but findings in the area of social cognitive (e.g., theory of mind, ToM) capacities have been heterogeneous. The aims of the current study were to investigate differences between patients with BPD and controls in functional connectivity (1) between the emotion and ToM network and (2) in the default mode network (DMN). Functional magnetic resonance imaging was used to investigate 19 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 77 publications
2
33
0
3
Order By: Relevance
“…It is expected that post-therapy neuronal activations are lower in a EP network involving areas in the PFC, the striatum and the insula-basal ganglia [57,58], when compared with pre-therapy. For post-therapy SCP, we expect lower CCRT pervasiveness, when compared with pre-therapy and we expect that post-therapy neurofunctional activations are lower in regions associated with the theory of mind (i.e., anterior cingulate, precuneus, inferior and middle frontal gyri and inferior parietal lobes) [69][70][71], compared with pre-therapy.…”
Section: Objectives {7}mentioning
confidence: 95%
See 1 more Smart Citation
“…It is expected that post-therapy neuronal activations are lower in a EP network involving areas in the PFC, the striatum and the insula-basal ganglia [57,58], when compared with pre-therapy. For post-therapy SCP, we expect lower CCRT pervasiveness, when compared with pre-therapy and we expect that post-therapy neurofunctional activations are lower in regions associated with the theory of mind (i.e., anterior cingulate, precuneus, inferior and middle frontal gyri and inferior parietal lobes) [69][70][71], compared with pre-therapy.…”
Section: Objectives {7}mentioning
confidence: 95%
“…Decrease in CCRT pervasiveness is an indicator of productive change. The fMRI task involves the appreciation of humoristic stimuli measuring the patient's theory of mind; this task has previously been validated for BPD [69] (for the validation of the stimuli see [80,81]). It involves the processing and understanding of three sets of stimuli, presented in a pseudo-random order: (1) The remaining assessments concern secondary outcomes and include the Outcome Questionnaire-45 [82], which is a self-report questionnaire comprising 45 items aiming at assessing psychotherapeutic results, including a global score and three sub-scale scores: symptomatic level, interpersonal relationships and social role.…”
Section: Outcomes {12}mentioning
confidence: 99%
“…O'Neill and colleagues [72] examined neural functional connectivity during a ToM task in a sample of 17 individuals with BPD and 19 HCs. In the task, participants had to rate whether or not they understood or did not understand humorous cartoons and non-humorous pictures (consisting of an incongruity that could not be meaningfully interpreted).…”
Section: Neural Network Tom and Bpdmentioning
confidence: 99%
“…As we argue in this project, a networkbased approach, focusing on the broader circuits at play such as the DMN, SN, and CEN is an important direction for BPD neuroimaging research and may help overcome the limitations of such a piecemeal literature. A few studies have already begun this work and find compelling evidence for the role that altered activation in these networks (measured using rs-fMRI, while the brain is not performing a specific task and is therefore considered at rest) plays in BPD pathology [72,92,185]. Additionally, we know that these neural regions and networks interplay in complex patterns in order to execute the processes associated with affect, cognition, and behavior and altered interactions between networks and regions likely underlies pathology.…”
Section: Using Functional Neuroimaging To Refine the Diagnostic Constmentioning
confidence: 99%
“…Moreover, studies using event-related measures such as fMRI have observed discrepant patterns of neural activation in the cognitive (Mensebach et al, 2009;Niedtfeld et al, 2017;O'Neill et al, 2015;Reitz et al, 2015) , behavioural (Herbort et al, 2016), social (Bungert et al, 2015;Domsalla et al, 2014;King-Casas et al, 2008) and affective processing (Bertsch et al, 2013;Hazlett et al, 2012;Lischke et al, 2017;Scherpiet et al, 2014) of BPD samples compared to healthy controls. However, it must be noted that the neurocircuitry of the disorderthough more PeerJ Preprints | https://doi.org/10.7287/peerj.preprints.27414v1 | CC BY 4.0 Open Access | rec: 5 Dec 2018, publ: 5 Dec 2018…”
Section: Introductionmentioning
confidence: 99%